A COMBINATION OF ENDORPHIN MASSAGE AND LAVENDER AROMATHERAPY CAN REDUCE PAIN LEVELS IN POSTPARTUM MOTHERS WITH CEPHALOPELVIC DISPROPORTION (CPD) IN HOSPITALS - Suryani Hartati; Amelia Fauziah (Poltekkes Kemenkes Banten, 2026)
Postpartum due to indication of Cephalopelvic Disproportion is an abnormal condition where the size of the mother's pelvis is not proportional to the size of the fetus. Cephalopelvic disproportion is characterized by the fetal head not entering the upper pelvic inlet at 40 weeks of gestation, so a cesarean section must be performed. After a cesarean section, there is severed tissue, which causes pain, and to reduce the pain, a combination of endorphin massage therapy and lavender aromatherapy is performed. The purpose of this scientific paper is to provide an overview of the effect of a combination of endorphin massage therapy and lavender aromatherapy on reducing pain with post-cesarean section indication of cephalopelvic disproportion (CPD). The research method of this paper uses a descriptive case study approach on mothers post-cesarean section. The study was conducted on April 29 - May 1, 2025, at the hospital. The results of the study obtained patient assessment data saying,